ER–endosome contact sites: molecular compositions and functions. (3rd June 2015) - Raiborg, Camilla; Wenzel, Eva M; Stenmark, Harald
Abstract Recent studies have revealed the existence of numerous contact sites between the endoplasmic reticulum (ER) and endosomes in mammalian cells. Such contacts increase during endosome maturation and play key roles in cholesterol transfer, endosome positioning, receptor dephosphorylation, and endosome fission. At least 7 distinct contact sites between the ER and endosomes have been identified to date, which have diverse molecular compositions. Common to these contact sites is that they impose a close apposition between the ER and endosome membranes, which excludes membrane fusion while allowing the flow of molecular signals between the two membranes, in the form of enzymatic modifications, or ion, lipid, or protein transfer. Thus, ER–endosome contact sites ensure coordination of molecular activities between the two compartments while keeping their general compositions intact. Here, we review the molecular architectures and cellular functions of known ER–endosome contact sites and discuss their implications for human health.